"Family neglect and its relationship to school bullying among middle school students" (Journal of the College of Basic Education, 2025)
The current research aims to identify family neglect and its relationship to school bullying among middle school students for the academic year 2024/2025. The sample consisted of (200) male and female students. The researcher prepared a scale of family neglect, which consisted of (25) paragraphs. The researcher adopted the (Al-Shaib Scale) for school bullying 2023, which consists of (30) paragraphs. The results showed that middle school students are not characterized by family neglect, but rather by a level of school bullying, and that the relationship between them is a direct correlation.